(Paleo)ecology of coccolithophores in the submarine canyons of the central portuguese continental margin:environmental, sedimentary and oceanographic implications - Guerreiro, Catarina Alexandra Vicente, 1978- (2013)
Tese de doutoramento, Geologia (Paleontologia e Estatigrafia), Universidade de Lisboa, Faculdade de Ciências, 2013